HUBUNGAN ANTARA INTIMASI PELATIH DENGAN ATLET DAN MOTIVASI BERPRESTASI TERHADAP KECEMASAN BERTANDING PADA ATLET UKM BOLA BASKET UNNES - Muhammad Farkhan Tri Negoro; Sungkowo Sungkowo (Universitas Negeri Semarang, 2023)
Anxiety is a worry about something unwanted will happen to someone. The type of research used is quantitative with a research design study of hypothesis submission. Data collection techniques using a questionnaire (questionnaire). Data analysis techniques consisted of descriptive analysis and Statistical Program for Social Science (SPSS) analysis. The results of the research statistically showed that there was a significant correlation between coach intimacy with athletes and achievement motivation on athlete's competition anxiety. Coach intimacy with athletes and achievement motivation on competition anxiety have a negative correlation. With the results of the hypothesis between coach intimacy with athletes of 0.210 with an R squared value of 0.420, the correlation between competition motivation is 0.803 with an R squared value of 0.116 and the correlation between coach intimacy and achievement motivation is 0.028 with an R squared value of 0.423. The conclusion of this study is that there is a correlation between coach intimacy with athletes on anxiety and a correlation between coach intimacy and athlete achievement motivation. There is no correlation between achievement motivation and competition anxiety